1986
DOI: 10.1021/i100021a009
|View full text |Cite
|
Sign up to set email alerts
|

Structure sensitivity of catalytic reactions

Abstract: The rate and product distribution of chemical reactions catalyzed by metals can depend on the particle size of supported catalysts. This can be explained by the interaction between chemisorbed species and surface sites of different configuration in the metal associated with atoms in terrace, steps, and kinks. Single-crystal catalysts are excellent models for studying these interactions. In this review, the contribution of single-crystal studies to the understanding of structure sensitivity in catalytic reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(99 citation statements)
references
References 26 publications
5
94
0
Order By: Relevance
“…Pt/SiO 2 , having an open porous structure, showed markedly higher activity than these samples. A previous study using Pt/SiO 2 as a model catalyst showed a monotonic increase of TOR with decreasing Pt cluster size in a range of 1. sites play an important role in the C-C bond breakage 23,24 . Because the Pt cluster sizes in the Pt-encapsulated catalysts and Pt/SiO 2 are comparable (B1.0 nm), as determined from the EXAFS analysis (Supplementary Table 1), all the catalysts are expected to show similar hydrogenolysis activity if the reaction occurs on the Pt cluster surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pt/SiO 2 , having an open porous structure, showed markedly higher activity than these samples. A previous study using Pt/SiO 2 as a model catalyst showed a monotonic increase of TOR with decreasing Pt cluster size in a range of 1. sites play an important role in the C-C bond breakage 23,24 . Because the Pt cluster sizes in the Pt-encapsulated catalysts and Pt/SiO 2 are comparable (B1.0 nm), as determined from the EXAFS analysis (Supplementary Table 1), all the catalysts are expected to show similar hydrogenolysis activity if the reaction occurs on the Pt cluster surface.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be emphasized again that the catalytic turnover rates in this work were calculated based on the total number of Pt rather than that of Pt accessible by H 2 or CO. For the minor external Pt species to cover the entire catalytic activities observed in the hydro-/ dehydrogenation reactions, their specific activity should be orders of magnitude higher than ordinary Pt species. Considering that the specific activities of Pt in hydro-/dehydrogenation have been reported to be relatively insensitive to Pt cluster size and shapes 24 , the assumption of the existence of 'super-active' Pt is unreasonable. Furthermore, the distinct chemoselectivity (suppressed hydrogenolysis) and the remarkable dependence of catalytic activity on the hydroxyl concentration of support surface cannot be explained by the conventional reaction mechanism on metal surface.…”
Section: Discussionmentioning
confidence: 99%
“…During the past decades, metal single-crystal surfaces have been widely adopted by surface scientists as model catalysts to systematically study the effect of surface structure on catalysis reactions, such as ammonia synthesis, isomerization of light alkanes, hydrogenolysis of alkanes and so on. [17][18][19] In order to gain a clear picture on the surface structure effect, such studies were typically performed in ultrahigh vacuum (UHV), leading to the pressure and material gaps between many model catalysis studies and real catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Still, catalytic reactions often occur preferably on surface steps and edges. 12 In this study, we use phenol as an oxygen-containing model component for biomass-based liquids. We will discuss the behavior of phenol on Pt(111), Rh(111) and stepped Pt and Rh surfaces based on periodic DFT calculations.…”
Section: Introductionmentioning
confidence: 99%